Theta Oscillations Reflect the Dynamics of Interference in Episodic Memory Retrieval - Staudigl, Tobias (J Neurosci, 2010)
Selectively retrieving episodic information from a cue often induces interference from related episodes. To promote successful retrieval of the target episode, such interference is resolved by inhibition, causing retrieval-induced forgetting of the related but irrelevant information. Passively studying the episodic information again (reexposure) does not show this effect. This study examined the hypothesis that brain oscillations in the theta band (5–9 Hz) reflect the dynamics of interference in selective memory retrieval, analyzing EEG data from 24 healthy human subjects (21 women, 3 men). High versus low levels of interference were investigated by comparing the effects of selective retrieval with the effects of reexposure of material, with the former, but not the latter, inducing interference. Moreover, we analyzed repeated cycles of selective retrieval and reexposure, assuming that interference is reduced by inhibition across retrieval cycles, but not across reexposure cycles. We found greater theta band activity in selective retrieval than in reexposure, and a reduction in theta amplitude from the first to the second cycle of retrieval predicting the amount of retrieval-induced forgetting; the sources of theta amplitude reduction across retrieval cycles were located in the anterior cingulate cortex. No difference in theta activity was found across repeated cycles of reexposure. The results suggest that higher levels of interference in episodic memory are indexed by more theta band activity, and that successful interference resolution via inhibition causes a reduction in theta amplitude. Thus, theta band activity can serve as a neural marker of the dynamics of interference in selective episodic retrieval.